Integrative hydrologic modelling of soil and water conservation strategies: a SWAT-based evaluation of environmental resilience in the Merguellil watershed, Tunisia - Hermassi, Taoufik; Jarray, Fathia; Tlili, Waad; Achour, Issam; Mechergui, Mohamed (Frontiers in Water, 2025)
IntroductionAnalyzing the hydrological dynamics and assessing the impact of Soil and Water Conservation (SWC) techniques provides crucial insights for developing region-specific conservation strategies and advancing effective watershed management.MethodsA multi-objective calibration concept was applied to the Soil and Water Assessment Tool (SWAT) model, where simultaneous calibration across the watershed andits sub-watersheds was performed using multiple objective criteria. This study investigates the impact of SWC measures on the hydrological dynamics of the Merguellil watershed, Central Tunisia. The research includes a sensitivity analysis, as well as the calibration and validation of the SWAT model, revealing seven sensitive parameters.Results and discussionDuring calibration (2000-2012), NSE was 0.82 and R2 was 0.9, RSR was 0.19 and PBIAS was 11.62%. In validation (2013–2020), NSE was 0.81 and R2 remained 0.9, RSR was 0.22 and PBIAS was 10.96%, indicating a strong correlation. Results of multi-watershed calibration were analyzed in two representative sub-watersheds (SW 8 and SW 16) and present good agreement between simulated and observed values. Simulating the SWAT model with and without SWC techniques reveals a consistent reduction in surface runoff, notably in central subbasins with values exceeding 15%. The observed decrease is attributed to vegetation cover, indicating the effectiveness of SWC practices. In contrast, subbasins lacking SWC interventions exhibit minimal runoff changes. The study further assesses the impact of SWC techniques on soil erosion, revealing negative percentage differences that indicate a reduction in erosion of over 30% following the implementation of these techniques. The central subbasins, marked by olive trees and strategic conservation, demonstrate substantial decreases, emphasizing successful erosion control efforts. Groundwater recharge analysis shows that SWC practices, along with favorable conditions, significantly enhance percolation and groundwater recharge, highlighting their beneficial impact. Variations in recharge percentages across subbasins reflect the nuanced responses influenced by anthropogenic and natural factors. Erosion hotspots were identified using sediment yield (SY) data. Six sub-watersheds were categorized from moderate to severe sediment severity classes and pinpointed as soil erosion hotspots, requiring immediate intervention. Finally, the study underscores the vital role of SWC techniques in mitigating surface runoff, reducing soil erosion, and enhancing groundwater recharge in the semi-arid Merguellil watershed. The findings emphasize the need for tailored conservation strategies considering geographical variations for effective watershed management and sustainability.